Scaffold-free: A developing technique in field of tissue engineering. (March 2020) - Alblawi, Adel; Ranjani, Achalla Sri; Yasmin, Humaira; Gupta, Sharda; Bit, Arindam; Rahimi-Gorji, Mohammad
Highlights: We proposed a cell sheet based bioprinting technique where mesenchymal stem cells (MSCs) on the surface of thermoresponsive polymer were subjected to mechanosensing either by introducing acoustic energies or stress created by polymeric strain energy function. Mechanosensing stimulus will trigger the intracellular signal transduction pathway leading to differentiation of the MSCs into desired cells. Abstract: Scaffold-free tissue engineering can be considered as a rapidly developing technique in the field of tissue engineering. In the areas of regenerative medicine and wound healing, there is a demand of techniques where no scaffolds are used for the development of desired tissue. These techniques will overcome the problems of rejection and tissue failure which are common with scaffolds. Main breakthrough of scaffold free tissue engineering was after invention of 3-D printers which made it possible to print complex tissues which were not possible by conventional methods. Mathematical modeling is a prediction technique is used in tissue engineering for simulation of the model to be constructed. Coming to scaffold-free technique, mathematical modeling is necessary for the processing of the model that has to be bio-printed so as to avoid and changes in the final construct. Tissue construct is developed by use of non-destructive imaging techniques i.e. computed tomography (CT) and magnetic resonance imaging (MRI).In this review, we discussed about various mathematical models and the models which are widely used in bioprinting techniques such as Cellular Potts Model (CPM) and Cellular Particle Dynamic (CPD) model. Later, developed of 3-D tissue construct using micro CT scan images was explained. Finally, we discussed about scaffold free techniques such as 3-D bioprinting and cell sheet technology. In this manuscript, we proposed a cell sheet based bioprinting technique where mesenchymal stem cells (MSCs) on the surface of thermoresponsive polymer were subjected to mechanosensing either by introducing acoustic energies or stress created by polymeric strain energy function. Mechanosensing stimulus will trigger the intracellular signal transduction pathway leading to differentiation of the MSCs into desired cells.